Comparison of Food Consumption and Health-Related Quality of Life Among Basketball Players of Different Competitive Levels; [Comparación del Consumo Alimentario y Calidad de Vida Relacionada Con la Salud Entre Baloncestistas de Distinto Nivel Competitivo] - Herrera-Valenzuela, T (Sociedad espanola de dietetica, 2023)
Introduction: Eating habits and mental health are fundamental aspects to optimize the preparation and sports performance of basketball players. Aim: To compare the frequency of food consumption and health-related quality of life (HRQoL) among basketball players of different competitive levels (professional, university, and amateur). Material and methods: Cross-sectional study that evaluated 122 male basketball players (mean age of 30.60 ± 10.79 years), divided into professional (JBP; n=25), university (JBU; n=26) and amateur (JBA; n=71). The study variables were evaluated through online surveys regarding the frequency of food consumption and HRQoL (SF-36). Results: The JBP show a significantly higher consumption of dinner (F= 5,007; p= 0,020) compared to the JBU, and of fruits (F= 5,857; p= 0,012), vegetables (F= 3,756; p= 0,020) and dinner (F= 5,007; p= 0,011) compared to the JBA. While the JBU present a significantly higher consumption of fruits (F= 5,857; p= 0,035) than the JBA. In addition, the JBU had a significantly higher consumption of sugary drinks (F= 9,293; p= 0,004) compared to the JBP and JBA. The HRQoL did not present significant differences between the groups. Conclusion: The JBP have a higher frequency in the consumption of healthy foods when compared to JBU and JBA. In addition, the JBU report a higher frequency in the consumption of sugary drinks compared to the JBP and JBA. While, the HRQoL is positive regardless of the competitive level of the basketball players. © 2023 Sociedad espanola de dietetica. All rights reserved.